Research practice for cultural studies : ethnographic methods and lived cultures - Gray, Ann, 1946- (SAGE, 2003)
How is culture 'lived'? What are the best ways of investigating cultural life? This book offers practical guidance for researching cultural studies.
Keywords: Culture -- Research.; Culture -- Study and teaching.; Social sciences -- Research -- Methodology.; Ethnology -- Methodology.; Culture -- Étude et enseignement.; Sciences sociales -- Recherche -- Méthodologie.; Ethnologie -- Méthodologie.; SOCIAL SCIENCE -- Research.; SOCIAL SCIENCE -- Methodology.; Culture -- Research; Culture -- Study and teaching; Ethnology -- Methodology; Social sciences -- Research -- Methodology; Sociaal-wetenschappelijk onderzoek.; Methodologie.; Etnografie.; Cultural studies -- Social research & statistics.